PENYULUHAN PENTINGNYA PEMBUATAN LABEL PRODUK UMKM DESA MAJAU KECAMATAN SAKETI - Ravindra Safitra hidayat; Yuwono Yuwono; Rizky Eka Prasetya; Elizabeth Elizabeth; Yugi Setyarko (Fakultas Ekonomi & Bisnis Universitas Jenderal Soedirman, 2024)
Abstract Product labels are essential for UMKM (Micro, Small, and Medium Enterprises) players because they help strengthen their identity and differentiate their products from competitors' products. Product labels also help customers understand the specifications and quality of the products they buy. This situation can influence customer purchasing decisions and improve the image of MSME products. The counseling activity on making MSME product labels in Majau Village, Saketi District, was carried out to increase the knowledge and awareness of MSME actors about the importance of making product labels for the sustainability and improvement of their business. Based on outreach activities, the results of pre-and post-test statistical data obtained showed a significant increase in the knowledge and awareness of MSME actors about the importance of making product labels. These results indicate that this socialization activity was successful in helping MSME actors to increase their business and strengthen their product information. This activity increased the knowledge and interest of the MSMEs in Majau Village in making product labels. This result is evident from the results of statistical data, which shows that the number of respondents who know the importance of product labels for MSMEs has increased after participating in socialization activities. Therefore, it is crucial to continue this socialization activity so that MSME actors can continue to develop and expand their product market